2022
DOI: 10.3389/fnut.2022.950446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arabinoxylan and chlorogenic acid on the intestinal microbiota in dextran sulfate sodium–treated mice

Abstract: Dietary non-starch polysaccharides and phenolics are usually ingested at the same time. They are both regarded as prebiotics, and they regulate the intestinal microbiota through various mechanisms. Notably, however, reports of their combined or synergistic effects are rare. Arabinoxylan (AX), a polysaccharide, and chlorogenic acid (CA), a polyphenol, are widely consumed, and their effects on the microbiota have previously been discussed. In the present study, they were given to dextran sulfate sodium (DSS)–tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, these changes varied in different experiments. 12,20,21 These inconsistent results indicate that the effects of DSS on gut microbes may also affect by host microbial composition and other factors. Nevertheless, cucurbitacin E supplementation alleviated the alterations caused by the DSS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes varied in different experiments. 12,20,21 These inconsistent results indicate that the effects of DSS on gut microbes may also affect by host microbial composition and other factors. Nevertheless, cucurbitacin E supplementation alleviated the alterations caused by the DSS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a previous study failed to determine a preventive effect against DSS-induced acute colitis, which is triggered by gut barrier destruction and subsequent innate immune cell activation [ 22 ]. The reason that AX did not affect DSS-induced colitis might be due to the low dosage of AX used in the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have demonstrated the beneficial effects of AX in IBD. Only one recent study has evaluated the impact of AX intervention on DSS-induced colitis, an IBD model triggered by an intestinal barrier disorder, followed by bacterial invasion and subsequent innate immune cell activation [ 22 ]. However, no conclusions have been drawn regarding the preventive effects of AX against colitis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, RBAC research has been featured in research characterising as a functional ingredient of defatted rice bran [ 58 ] and a fermented rice bran by-product with anticancer properties [ 22 , 59 61 ], as a polyphenolic compound based on hemicelluloses [ 62 ] or polysaccharides [ 63 ] beneficial for gastrointestinal disorders and cancer [ 64 ], and as natural food to protect against gamma-induced oxidative damage [ 65 ]. RBAC is also commonly cited as a representative arabinoxylan in the diverse group of dietary fibres that exist in food [ 66 ] with anticancer and antioxidant effects [ 67 ] and the capacity to modulate gut microbiota [ 68 ] for combating human chronic diseases [ 69 ]. Results from RBAC research also affected the research design of oncological experimental models [ 70 ], especially in preventing tumour growth [ 71 ].…”
Section: Discussionmentioning
confidence: 99%